Gender Differences in Spiritual Experiences, Religious Practices, and Congregational Support for Individuals with Significant Health Conditions - Reid-Arndt, Stephanie A. (Journal of religion, disability & health, 2011)
This study sought to identify gender differences among medical patients for their spiritual/religious beliefs/practices and their associations with health. Patients (N = 168) completed the Brief Multidimensional Measure of Religiousness/Spirituality (BMMRS), and SF-36 general health perception (GHP) and general mental health (GMH) scales. No gender differences were found in endorsement of spiritual experiences, religious practices, or congregational support. For men, religious/spiritual coping significantly correlated with GHP and GMH, and religious support significantly correlated with GMH. For women, measures of spiritual experiences, religious practices, and congregational support were significantly correlated with GMH, but no significant correlations with GHP were noted. Regression analyses revealed that the interaction between gender and BMMRS was a significant predictor for GMH and GHP. Follow-up analyses suggested that for women, GMH was associated with religious/spiritual coping, religious support, daily spiritual experiences, forgiveness, and organizational religion. In contrast, GHP was only significantly predicted by religious support and only for men. Although no gender differences were noted in endorsement of religious/spiritual experiences/practices, gender differences in relationships between spirituality beliefs/practices and health may exist among individuals with chronic health issues.